Studies on the Effect of Pollutant Waste on Free Radical Content in Tilapia Gill Organs (Oreochromis Niloticus) - Nindha A. Berlianti; Chomsin S. Widodo; Unggul P. Juswono (Natural B, Journal of Health and Environmental Sciences, 2014)
Studies on the effect of heavy metal pollution on the appearance of free radicals in aquatic biota has been done by applying heavy metals Pb, Cd and Hg in tilapia fish (Oreochromis Niloticus). Free radicals research was done to organ of tilapia gills using ESR. The result showed that the concentration of Pb Nitrate 0.2 ppm – 1.4 ppm, Cd Nitrate 0.02 ppm – 0.14 ppm and Hg Nitrate 0.006 ppm – 0.018 ppm could improve free radical O2-. Free radicals concentration in organ of tilapia gills will increase with increasing concentration of heavy metals.